Comparing Linear A and Linear B administrative systems: the case of the roundel and the elongated tablet - Tomas, Helena (Array, 2008)
With the disappearance of Linear A a prominent Minoan type of document - the roundel - vanished completely. The nascent Linear B system did not use it even in its transitional phase from Linear A. However, A new Linear B type of document - the elongated tablet - displays some similarities with the roundel, conseqently their possible link is explored in this paper.